Phylogenomic Analysis of the Gammaproteobacterial Methanotrophs (Order Methylococcales) Calls for the Reclassification of Members at the Genus and Species Levels - Orata, Fabini D.; Meier-Kolthoff, Jan P.; Sauvageau, Dominic; Stein, Lisa Y. (Frontiers in Microbiology, 2018)
The order Methylococcales constitutes the methanotrophs – bacteria that can metabolize methane, a potent greenhouse gas, as their sole source of energy. These bacteria are significant players in the global carbon cycle and can produce value-added products from methane, such as biopolymers, biofuels, and single-cell proteins for animal feed, among others. Previous studies using single-gene phylogenies have shown inconsistencies in the currently established taxonomic structure of this group. This study aimed to determine and resolve these issues by using whole-genome sequence analyses. Phylogenomic analysis and the use of similarity indexes for genomic comparisons – average amino acid identity (AAI), digital DNA–DNA hybridization (dDDH), and average nucleotide identity (ANI) – were performed on 91 Methylococcales genomes. Results suggest the reclassification of members at the genus and species levels. Firstly, to resolve polyphyly of the genus Methylomicrobium, Methylomicrobium alcaliphilum, “Methylomicrobium buryatense”, Methylomicrobium japanense, Methylomicrobium kenyense, and Methylomicrobium pelagicum are reclassified to a newly proposed genus, Methylotuvimicrobium gen. nov.; they are therefore renamed to Methylotuvimicrobium alcaliphilum comb. nov., “Methylotuvimicrobium buryatense” comb. nov., Methylotuvimicrobium japanense comb. nov., Methylotuvimicrobium kenyense comb. nov., and Methylotuvimicrobium pelagicum comb. nov., respectively. Secondly, due to the phylogenetic affinity and phenotypic similarities of Methylosarcina lacus with Methylomicrobium agile and Methylomicrobium album, the reclassification of the former species to Methylomicrobium lacus comb. nov. is proposed. Thirdly, using established same-species delineation thresholds (70% dDDH and 95% ANI), Methylobacter whittenburyi is proposed to be a later heterotypic synonym of Methylobacter marinus (89% dDDH and 99% ANI). Also, the effectively but not validly published “Methylomonas denitrificans” was identified as Methylomonas methanica (92% dDDH and 100% ANI), indicating that the former is a later heterotypic synonym of the latter. Lastly, strains MC09, R-45363, and R-45371, currently identified as M. methanica, each represent a putative novel species of the genus Methylomonas (21–35% dDDH and 74–88% ANI against M. methanica) and were reclassified as Methylomonas sp. strains. It is imperative to resolve taxonomic inconsistencies within this group, first and foremost, to avoid confusion with ecological and evolutionary interpretations in subsequent studies.